Is the habit system altered in individuals with obesity? A systematic review. (September 2021) - Ciria, Luis F.; Watson, Poppy; Vadillo, Miguel A.; Luque, David
Highlights: Current evidence does not support an imbalance of reward learning systems in obesity. Existing studies on habit and obesity implement a variety of different paradigms. We discuss commonalities between eating behavior and drug-addiction. We suggest specific ways for improving the research on this topic. Abstract: Habit-like eating behavior is repeatedly pointed to as a key cognitive mechanism contributing to the emergence and maintenance of obesity. Here, we conducted a systematic review of the literature to assess the existent behavioral evidence for the Habit Hypothesis for Overeating (HHO) which states that obesity is the consequence of an imbalance between the habit and goal-directed reward learning systems, leading to overconsumption of food. We found a total of 19 studies implementing a variety of experimental protocols (i.e., free operant paradigm, slips-of-action test, two-step task, Pavlovian-to-Instrumental paradigm, probabilistic learning task) and manipulations. Taken together, the studies on clinical (binge eating disorder) and non-clinical individuals with overweight or obesity do not support the HHO conclusively. While the scientific literature on HHO is still in its infancy, the heterogeneity of the extant studies makes it difficult to evaluate the degree of convergence of these findings. Uncovering the role of reward learning systems in eating behaviors might have a transformative impact on public health.